A Survey on Secure and Verifiable Access Control Scheme for Enormous Information Storage In Clouds - S. Akshaya Subhasri, R; Ranganayaki, M; Ulaga Priya, K; Kalaivani, K; Sartiha, A (International Journal of Engineering and Technology, 2018)
A secure and verifiable access control scheme for enormous information storage in cloud is based on Â open source public-key cryptosystem that uses lattice-based cryptography to encrypt and decrypt data .To overcome the decryption failures of the original LLL, the NTRU decryption algorithm is analysed. It allows to analyze it correctness, accuracy, security qualities and computational effectiveness. When a new entry permission is granted by the data users. It allows the cloud main system to update the cipher method details. It also able to update the counter against the hacking behavior on the cloud. It includes the data holder and eligible users who need to check the data user for accessing the data, the user check the content given by the next user for accurate plain text recovery. Through test shows, this scheme can prevent qualified user against hacking together with some other different raidÂ such as scam attacks.Â Â